The dollar and special drawing rights - W. J. Feuerlein (Intereconomics, 1979)
The IMF's Interim Committee recently for the first time discussed the creation of a “Substitution Account” to convert certain amounts of excess reserve currencies into SDRs. This issue is likely to be on the agenda of the next annual meeting of the IMF in the fall of this year. Prof. Feuerlein discusses the problems of such an account.
Keywords: 330; Monetary Policy